The Effectiveness Of Adaptive Training Programs In Improving The Physical Fitness Of Chlidren With Special Needs - Reno Faldi Guntur Saputra Sinaga; Anisa; Tiara Salsabillah Janna; Regita Nathasa Br Kemit; Yan Indra Siregar; Ahmad Syabaruddin (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to examine the effectiveness of adaptive training programs in improving the physical fitness of children with special needs by implementing an adaptive physical education learning model for students with special needs. The adaptive learning model is used to examine the effectiveness of adaptive training programs in improving the physical fitness of children with special needs. The research method used was an experiment with a one-group pretest-posttest design. The research subjects were a number of children with special needs who participated in an adaptive training program for a certain period. The data collection instrument was a physical fitness test that included strength, endurance, agility, and flexibility. Data analysis was performed using statistical tests to compare the results before and after the treatment. The results showed a significant improvement in physical fitness after participating in the adaptive training program. These findings indicate that adaptive training programs are effective in helping children with special needs improve their physical condition, while also providing psychological benefits in the form of increased self-confidence and motivation to be active. Thus, adaptive training programs can be used as an alternative approach to inclusive physical education that is oriented towards individual needs.